Protocol for pulsed antihydrogen production in the AEḡIS apparatus. (August 2020) - Tietje, I C; Amsler, C; Antonello, M; Belov, A; Bonomi, G; Brusa, R S; Caccia, M; Camper, A; Caravita, R; Castelli, F; Cheinet, P; Comparat, D; et al.
Abstract: The AE ḡ IS collaboration's main goal is to measure the acceleration of antihydrogen ( H ¯ ) due to gravity. The experimental scheme is to form a pulsed beam whose vertical deflection is then measured by means of a moiré deflectometer [1]. Creating pulsed H ¯ is crucial since it allows a velocity measurement of the antiatoms via time of flight (ToF) necessary to deduce the gravitational acceleration ḡ from the vertical deflection Δ s . The aim of this article is to outline the experimental protocol leading up to pulsed antihydrogen production in the AE ḡ IS experiment.